Identidades profissionais docentes: contribuições da formação inicial - Barbosa, Anna Carolina Leopoldino (2023)
The research aimed to show, based on the theoretical discussion, the documents analyzed, the data collected in the interviews and their respective interpretation, that, in general, the curricula in licentiate deal only with essential points and the issues of educational networks are treated superficially. Therefore, what is offered in the courses is a superficial pedagogical training that does not train teachers to work in schools today. There is a formative insufficiency on the real understanding of the teacher and the school institution itself. The research problem arises from the analysis of the principles and processes that regulate the construction of the professional identity of teachers who work in basic education in the Municipality of Santo André and the relationship with their initial training in their professional performance in basic education. The question regarding the research problem, which guided us, was the following: how do professors build their professional identities, at the confluence of other identities, primarily personal and institutional identities? How do they deal with those combined with the marketing vision of education and knowledge? And how are identities reformulated, reconstructed according to the changes that are taking place in the teaching profession in basic education with the requirement that it adjusts to political objectives? From an epistemological point of view, we adopted a theoretical-epistemological model in line with critical theories, as we believe that the issue of basic education teachers´ professional identity is indissolubly linked to the problem of the quality of initial education and to what is intended to be a basic education of quality. Methodologically, we adopted a qualitative approach, using interviews as a data collection instrument and discourse analysis as a data analysis technique. The analysis carried out allowed us to state that the professional identity of teachers is constructed according to the demands of the educational sectors in today’s society. The empirical work carried out allowed us to conclude that the thesis from which we started is confirmed, that is, there is a relationship between the construction of professional identities, teaching professionalism and initial training, which is understood by the subjects, above all, as professional qualification.